A critical analysis of the statutory framework on maintenance of non-muslim children and young persons in Malaysia / Sridevi Thambapillay - Sridevi , Thambapillay (2017)
A family unit is the basic unit in a society. The collapse of a family unit will ultimately lead to the collapse of the society. In a family unit comprising of a man, his wife and child, the child is the most vulnerable person, as he has to depend on his parents for his survival. The parents have a responsibility towards the child, one of which is to maintain the child. The parents have a legal as well as a moral duty to maintain their child. Breach of the moral duty will not attract any penalties whereas breach of a legal duty would. In Malaysia, there are two systems of maintenance laws:- one for the Muslims and one for the non-Muslims. This thesis, as the title states, examines the non-Muslim maintenance laws. There are about five maintenance laws, which are in force currently for the non-Muslims.